2009
DOI: 10.1080/07370010903259162
|View full text |Cite
|
Sign up to set email alerts
|

Reducing MRSA Infections in College Student Athletes: Implementation of a Prevention Program

Abstract: An interventional prevention program, Training CAMP Program, was implemented with college football players (n = 98) in a Midwestern NCAA Division II college during the 2008 college football season. The program goal was a 50% reduction in community-acquired Methicillin-resistant Staphylococcus aureus (CA-MRSA) cases, as compared to the previous 3 seasons' average number of cases (12.6). Results showed a greater than 75% reduction in CA-MRSA in the target population, with only 3 cases recorded for the entire 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…In a 2009 study of such measures as providing education booklets, posters and videos to college athletes, results showed a 75% reduction in infections. (172) This study was not a randomized controlled trial; it was based more on a theoretical framework and only evaluated absolute number of cases.…”
Section: Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…In a 2009 study of such measures as providing education booklets, posters and videos to college athletes, results showed a 75% reduction in infections. (172) This study was not a randomized controlled trial; it was based more on a theoretical framework and only evaluated absolute number of cases.…”
Section: Educationmentioning
confidence: 99%
“…The program consisted of three components (a) an educational session for players and coaches/trainers (b) educational booklets and posters, and (c) strategically placed MRSA deterring hand-sanitizing wipes. Over the course of the study it was shown that this program had reduced the number of CA-MRSA or SSTI by 9.6 cases (>75%) (172). Authors of the same study also tried to assess costeffectiveness of the program.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Thus, athletes may have more opportunity to contact CA-MRSA due to increased skin-to-skin contact and shared athletic equipment. 3,4,6,[8][9][10][11] Health care providers promote efforts to prevent CA-MRSA infection by improving hygiene and education in both the hospital and community environments. 11 In the athletic environment, athletic trainers (ATs) provide health care to athletes, including attempts to reduce potential infections such as CA-MRSA, yet recent studies indicate that CA-MRSA is still prevalent in athletic facilities 12,13 and that cleaning methods may not be optimal.…”
mentioning
confidence: 99%
“…Accordingly, much of the research found contact to be a component (Beiger et aI., 2004;9 Lindenmayer et aI, 1998;Sanders, 2009;Stacey et aI., 1998). The NCAA reported that from 2011 to 2012 most female student athletes participate in outdoor field and track, a non-contact sport, while most males participated in football (NCAA, 2013).…”
mentioning
confidence: 99%